THE GLOBAL EARTH GRAVITY FIELD MODEL UTILIZATION IN THE LITHOSPHERE STRUCTURE DEPICTION ON THE SUMATERA-JAVA SUBDUCTION ZONE - GAUS (NIM : 25109301); pembimbing: Dr.Ir. Kosasih Prijatna, M.Sc. ; Dr.Ir. Dina Anggreni Sar, KATHYA
In this study, the depiction of lithosphere structure on the Sumatera-Java subduction zone is done based on two global earth gravity field models, i.e ITG-Grace2010s from GRACE satellite and go_cons_gcf_2_tim_r3 from GOCE satellite, on two study areas that represent the Sumatera-Java subduction zone. Both model is derived from pure gravity satellite data, that is without terrestrial data, altimetry data, or the other gravity satellite data. Structure depiction is done on several harmonic degree truncation so the influence of harmonic degree in structure depiction can be known. Gravity anomaly derived from each models is inverted to density anomaly which show the lithosphere structure down to 100 kilometers depth. On the low degree, GRACE satellite yields more accurate lithosphere structure than GOCE satellite with deviation standard of 0.01648075 gr cm-3 for Sumatera study area and 0.0284079 gr cm-3 for Java study area. Meanwhile, on the high degree, GOCE satellite yields more accurate lithosphere structure than GRACE satellite with deviation standard of 0.01887206 gr cm-3 for Sumatera study area and 0.0712685 gr cm-3 for Java study area.